Operation of wastewater treatment plants : a field study training program (Sacramento : University Enterprises, Inc., 2008)
Resource added for the Environmental Engineering Waste and Water Technology program 105062.
The treatment plant operator -- Why treat wastes? -- Wastewater treatment facilities -- Racks, screens, comminutors, and grit removal -- Sedimentation and flotation -- Trickling filters -- Rotating biological contactors -- Activated sludge (package plants and oxidation ditches) -- Wastewater stabilization ponds -- Disinfection processes.
Keywords: WATER-SUPPLY ENGINEERING -- FIELDWORK -- HANDBOOKS, MANUALS, ETC